Influence of soil texture, climate and vegetation cover on secondary soil salinization in pampas plains, South America. - Milione, German; Mujica, Claudio; Dominguez Daguer, Diego; Bea, Sergio; Fernandez, María Elena; Gyenge, Javier (Universidad Federal de Lavras; Brasil., 2020)
Land-use change from herbaceous to woody cover -or vice versa- largely affects water fluxes, which in turn can mobilize existing salts dissolved in the soil, and thereby negatively affect soil and/or water quality and site productivity. The objective of this study was determine the occurrence of the soil salinization process associated to the afforestation in the Austral Pampas, considering the differences in water balance, soil texture and the presence of petrocalcic horizons that differ from the sites where secondary salinization was observed at the Northern and Eastern subregions of the Río de la Plata Grassland. Also, we determined which biological factors (tree species, age of plantation, plantation density and stand basal area) are associated with secondary salinization. The lowest EC values were found in sites with sandy-textured soils and negative water balance, regardless of vegetation cover. When EC differences did occur between land uses of the same site (50% of the sites), in most cases – but not in all of them – the highest EC was measured under tree cover. When salinization was significant, no pattern was observed in the soil profile where it was observed. An increase of EC was associated with the oldest-unmanaged plantation, with a mean age of 40 years, a period much longer than the productive rotation recommended. Under similar edaphic conditions where salinization was observed (i.e. clayed soils, with naturally high salt level), salinization was not significant in relatively young plantations (<rotation period), demonstrating the key role of forest management to decrease its negative impacts on soils.